2021
DOI: 10.1101/2021.11.04.467236
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geographical Distribution of Biomphalaria snails in East Africa

Abstract: There is limited information on the distribution of B. pfeifferi, an important snail intermediate host of schistosomiasis, in East Africa. This study assessed the incidence and geographical distribution of B. pfeifferi snails in Kenya, Uganda and Tanzania. Maximum Entropy modeling was used to predict the potential distribution of B. pfeifferi snails, in line with habitat suitability. Malacological surveys were then conducted guided by MaxEnt predictions and information obtained from previous research papers. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…In our study, with an NDVI range of 0.18 to 0.83 and an LST range of 3.4 to 43.6 °C in the region, both parameters exhibited low significance in determining the distribution of both genera (by MDG). This observation aligns with previous studies conducted by Magero et al 26 , Boitt and Suleiman 56 , and Deka 46 , all of which found a similar limited influence of these two parameters on the presence of IH snails. Nonetheless, it is important to consider that we have observed in this study that land cover has a limited influence at all.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, with an NDVI range of 0.18 to 0.83 and an LST range of 3.4 to 43.6 °C in the region, both parameters exhibited low significance in determining the distribution of both genera (by MDG). This observation aligns with previous studies conducted by Magero et al 26 , Boitt and Suleiman 56 , and Deka 46 , all of which found a similar limited influence of these two parameters on the presence of IH snails. Nonetheless, it is important to consider that we have observed in this study that land cover has a limited influence at all.…”
Section: Discussionsupporting
confidence: 93%
“…The land cover classification employed in this study distinguishes 17 land cover classes, including 11 natural vegetation classes (such as forests, open herbaceous areas, and wetlands), 3 human-altered classes (comprising agricultural land and built-up areas), and 3 non-vegetated classes (including snow, rocks, and water bodies). Furthermore, various physiochemical properties previously studied for their effects on IH snail distribution 14 , 26 , 46 were integrated into our analysis. This included soil pH, soil organic carbon content in fine earth, and soil cation exchange capacity obtained at a 30 m resolution at a depth of 0–20 cm and 20–50 cm from the Innovative Solutions for Decision Agriculture Ltd (iSDA) data set via Google Earth Engine 47 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomphalaria snails serve as the obligate intermediate host of Schistosoma mansoni, a parasitic blood uke that causes intestinal schistosomiasis [1, 2, 3]. Biomphalaria pfeifferi is commonly found in East Africa (e.g., Kenya, Uganda and Tanzania [4,5]). However, until this report, its presence in the Lower Shire River valley was unknown.…”
mentioning
confidence: 99%